Violence Against Children: Physical Exploitation Faced by Child Scavengers in Rural Islamabad-Pakistan - Dr. Nasim Khan Mahsud; Dr. Nudrat Mushtaq; Shabana Muhammad Anwar (Journal of Management Practices, Humanities and Social Sciences, 2022)
Street child is the challenging social phenomenon confronted by many nations across the globe. The phenomenon of child violence specifically among street children who are working like child scavengers exists in almost all big cities of Pakistan. The under-age children sent to work often face physical, emotional, and sexual violence as the working environment is unsupportive of child rights. This study is an explorative study to unfold the awareness level among study respondents about the phenomena of violence against children and various forms of physical violence they face at work. This explorative study was conducted in the rural Islamabad. By using the nonprobability sampling procedure, purposive sampling technique was opted for the current research. The sample size was 110 from which 91 male respondents aging from 12 years to under 18 were interviewed. The analysis was done in the form of percentages and frequency distribution cross tabs and chi square test was run by using SPSS. Findings of this explorative study reveals that these child scavengers are in more miserable conditions than any other group of children in the country. They become victims of physical violence on streets from their peer group, at their workplace from community people and also from their family members at homes with a very frequent intensity. Current study suggests serious interventions for child protection from violence as well as from hazardous work environment from government and other stakeholders i.e., local communities, NGOs, families so can provide a safe and healthy environment to our children which in return ensures sustainability of the productive society.